Fano Resonances in the Time Domain. (August 2015) - Kaldun, A; Ott, C; Stooß, V; Fischer, A; Blättermann, A; Ding, T; Raith, P; Meyer, K; Laux, M; Evers, J; Keitel, C H; Greene, C H; et al.
Synopsis: The Fano phase formalism enables measurement and control of phase and amplitude of an emitting dipole. Here, we use this formalism to measure and understand the dynamics of bound atomic states in strong laser fields.